Peningkatan Faktor Penuaan Arester Tanpa Sela Isolasi Polymer Akibat Kontaminan Kalsium Karbonat - Novizon, Novizon; Nofriadi, Nofriadi; Yustasia, Dano (JURNAL NASIONAL TEKNIK ELEKTRO, 2020)
Gapless arester leakage current can be used as an indicator to determine the aging level of the arester. Leakage current is influenced by contaminants present in the arester insulation. This paper analyzes the effect of contamination on arester leakage currents as an indicator of arester aging. Contaminants used are calcium carbonate plus kaolin dissolved into water, to determine the level of calcium carbonate contaminants, the ESDD (Equivalent Salt Deposit Density) method is used. Contaminated aresters are measured as leakage currents flowing to the block elements and to the arester insulation. Based on experiments that have been carried out, the increase in leakage current of the arester on the block element that increases the leakage current to the level of light, medium and heavy contamination rises by an average of 17.5% for the voltage of all test voltages. While at low and moderate contamination the leakage current that occurs in the polymer arester insulation does not significantly change, the leakage current generated is linear with the level of contaminants in the arester body. It can clearly be concluded that the effect of contamination is very significant in changes in leakage currents.Keywords : Gapless arester, Leakage current, Kontamination, Aging,Â AbstrakArus bocor arester tanpa sela dapat digunakan sebagai indikator untuk menentukan tingkat penuaan arester. Arus bocor dipengaruhi oleh kontaminan yang ada pada isolasi arester. Paper ini menganalisa pengaruh kontaminasi terhadap arus bocor arester sebagi indikator penuaan arester. Kontaminan yang digunakan adalah kalsium karbonat di tambah kaolin yang di larutkan kedalam air, untuk menentukan tingkat kontaminan kalsium karbonat maka digunakan metode ESDD (Equivalent Salt Deposit Density). Arester yang sudah berkontaminasi diukur arus bocor yang mengalir pada elemen blok dan pada isolasi arester. Berdasarkan percobaan yang telah dilakukan, kenaikan arus bocor arester pada elemen blok bahwa kenaikan arus bocor untuk tingkat kontaminasi ringan,sedang dan berat naik rata-rata 17.5 % untuk semua tegangan uji. Sementara pada kontaminasi rendah dan sedang arus bocor yang terjadi pada isolasi polimer arester tidak. singnifikan perubahannya,Arus bocor yang dihasilkan linier dengan tingkat kontaminan pada badan arester. Secara jelas dapat disimpulkan bahwa pengaruh kontaminasi sangat signifikan dalam perubahan arus bocor.Kata Kunci : Arester tanpa sela, Arus bocor, Kontaminasi, Penuaan,